The influence of the Andes mountains on the South American low-level flow - Campetella, Claudia Marcela (2002)
[1] A dry, hydrostatic, three-dimensional primitive equation model is used to evaluate the mechanical effect of the Andes mountains on the South American low-level flow (LLF). The model simulations reproduce the evolution of a baroclinic wave over the continent under winter and summer conditions. In both seasons as a consequence of the interaction between the basic flow and the Andes, northerly LLF was reproduced east of the Andes which resembles the main characteristics of the observed flow. Moreover, seasonal changes of cyclone activity have a significant impact on the location of maximum LLF and its alignment, which exhibits a NW-SE orientation during winter and more meridional orientation in the warm season.